(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
The English language is one of the most widely spoken languages in the world today. It serves not only as a native language for many but also as a global lingua franca in various contexts, including business, education, and international communication. This article explores the history, evolution, and significance of the English language